On locating the experiences of second year science students from rural areas in Higher Education in the field of science: lived rural experiences - Madondo, Nkosinathi Emmanuel (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2020)
This study was designed to investigate the experiences of Second Year Science students who come from rural backgrounds within a Higher Education context. The purpose of the study was to understand the enabling and/or constraining factors that influence the teaching and learning of Second Year Science students who come from rural contexts. Given this purpose, the participants that were considered relevant to answer the question: What are the enabling and constraining factors that influence teaching and learning of second year Science students who come from rural backgrounds at a South African University? were students from rural areas enrolled in the Faculty of Science at the research site, academic teachers and senior leaders', and roles in providing enabling and/or constraining teaching and learning environment. The phenomenon under investigation was thus, the extent to which the teaching and learning environment, in the field of science, enable or constrain access to the Discourse of science for students who come from rural areas. To generate data, the study used focus group discussions, Participatory Learning and Action (PLA) tools as part of Participatory Action Research (PAR), digital documentaries, as well as academic teachers' rich descriptions of the rationale for the design and delivery techniques of their modules by means of focus group interviews, as well as curriculum review documents. The purpose of Action Research (AR) in this study was to enable change by way of advancing a self-consciousness, envisaged to yield some action based on the enablements or constraints identified by the participants involved. Archer's (1995, 1996) analytical dualism was used as the analytical framework to identify the interplay of structural, cultural and agential mechanisms shaping the emergence of, and practices associated with students' experiences of the science curriculum and academic teachers' observations of these experiences. Bernstein's pedagogic device was also used to explain the options that academic teachers have to shape the curriculum, a curriculum that would reflect the experiences of the heterogeneity of the student cohort when designing their course guides, for example. The analysis thus used Archer's (1995, 1996) Morphogenesis/Morphostasis framework through which change or non-change can be observed over time. The work of Bhaskar (1975, 1979) was important in this regard because it allows us to separate what we see, experience and understand (in the transitive world) from what is independent of our thoughts and experiences (the intransitive world) when conducting scientific enquiry, so that we are able to deduce the 'real' factors that enable and constrain the events and experiences being studied. Since there are multiple mechanisms operative that can act to include or exclude students in Science classrooms, particularly those who come from lower class, including those who come from rural areas, this study focuses on curriculum as one mechanism that can be at play in the problem of exclusion. In this study, I argue, the University and its structures like curriculum are not neutral but are historical, cultural, political and social, which is why persistent apartheid legacy and coloniality were seen as playing a role in how the curriculum is designed and thus enacted. This is the reason, a decolonial gaze was adopted in order to engage with social justice issues and in the process tease out the social relations of knowledge practices. A decolonial gaze provided a way to re-describe the structuring of the curriculum and the contradictions it sets up for black students, particularly those who come from lower class backgrounds, including those from rural areas. Findings reveal that the way in which the science curriculum (and/or teaching and learning) is structured, and thus enacted, tends to favour certain worldviews to the exclusion of others. Also, findings show that when students are presented with knowledge that seems completely separate from them, their identities, their heritage, their backgrounds and value systems, accessing that knowledge can seem inordinately difficult. Consequently, students from rural contexts are often alienated, because the "world" they bring and know is often not considered part of the starting point, neither is it seen as relevant when teaching the science curriculum. There is therefore a clear need to bring something 'from home' into our teaching as a means of reassuring students that all is not foreign and that what they already know is valuable.
Keywords: Science students -- South Africa; Rural college students -- South Africa; Science -- Study and teaching (Higher) -- South Africa; Curriculum change -- South Africa; Learning -- Evaluation; Social justice and education -- South Africa; Action research in education -- South Africa; Participant observation -- South Africa; Critical realism; Ethnoscience -- South Africa; Focus groups -- South Africa; Bernstein, Basil